Ternary W-Ni-Fe tungsten heavy alloys: A first principles and experimental investigations. (September 2018) - Pathak, Ashish; Panchal, Ashutosh; Nandy, T.K.; Singh, A.K.
Abstract: Present work describes the mechanical behaviour of three virtual alloy systems comprising of matrix phase and W grains with fcc-bcc interface. The properties are evaluated for a composite tungsten heavy alloy. The compositions of the matrix phase have been considered similar to different tungsten heavy alloys (WHAs). The energy of the alloy systems decreases with increase in W contents. The lattice parameters of the matrix phase of WHAs are good agreement with those of the matrix phase of the virtual systems. The values of lattice constant, strength parameters (0.2 and 9% strain) and modulus increase with increase in W content. The nature of theoretical stress – strain curves of systems are similar to typical experimental ones. The addition of W increases the strength values and also shifts flow behaviour with higher strengths as function of strain. The yielding starts in typical WHAs in matrix phase only. Highlights: The energy of the alloy systems decreases with increase in W contents. Lattice constant, strength parameters and modulus increase with increase in W content. Nature of theoretical stress – strain curves of systems are similar to experimental ones. The yielding starts in typical WHAs in matrix phase only.